Оцінка показників стереоендоскопічних систем в ринології - Сокольцов, A.О.; Аврунін, О.Г.; Коваль, Л.Г.; Кадук, О.В. (Vinnytsia National Technical University, 2024)
This research examines the advantages and disadvantages of 3D endoscopy compared to traditional 2D endoscopy for sinus surgery. It has been found that 3D endoscopy significantly improves depth perception, the brightness of the surgical field, and intraoperative visualization, making it particularly useful for training and understanding anatomy. Despite these benefits, 3D endoscopy can cause discomfort in surgeons, including dizziness, eye strain, and headaches. The development of automated visualization systems based on stereo cameras can enhance procedural accuracy. The use of personalized physical models created through rapid prototyping increases the effectiveness of training systems. However, the need to wear 3D glasses and the difficulty in cleaning the lenses remain issues. Future prospects include the application of such systems in telemedicine services for remote consultations.